Development and Validation of Liquid Chromatography-Tandem Mass Spectrometric Method for Quantification of Meropenem in Rat Plasma and its Application in a Preclinical Dose Proportionality Study - Chaursia, B. K.; Singh, T. P.; Varshney, B.; Sharma, P.; Iyer, S. S.; Khuroo, A. H.; Monif, T. (Drug Research, 2014)
A simple, rapid, sensitive and selective assay based liquid chromatography-tandem mass spectrometric method was developed and validated for quantitative analysis of meropenem in rat plasma using rolipram as internal standard. Efficient chromatographic separation of analyte from matrix components was achieved by using Kromasil 100 C18 (150×4.6 mm, 5 µm) reversed phase column with mobile phase consisting of acetonitrile and 2 mM ammonium acetate buffer (80:20, v/v) delivered in isocratic mode with constant flow rate of 0.7 mL/min. Detection of meropenem and rolipram was performed in positive mode using multiple reaction monitoring (MRM). The mass transitions 384.1→141.0 and 276.2→191.1 were used to quantify meropenem and rolipram, respectively. A fast and simple solid phase extraction method was optimized for extraction of meropenem from rat plasma. The developed method was validated for selectivity, accuracy, precision, linearity, recovery, stability, matrix effect, dilution integrity as per regulatory guidelines. The developed method was selective with no interfering components at the retention time of meropenem and rolipram. The assay demonstrated acceptable linearity (R2>0.99) over a dynamic range of 0.19–201.40 µg/mL. The method exhibited excellent and acceptable precision and accuracy, and produced consistent recoveries. The method demonstrated excellent stability of meropenem in rat plasma under studied conditions investigated. Finally, the validated method was successfully applied to quantify meropenem levels in rat plasma of a dose escalation study.
Keywords: meropenem; solid phase extraction; validation; rat plasma; dose proportionality study; LC-MS/MS